2017
DOI: 10.3390/ijerph14020134
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5-Induced Oxidative Stress and Mitochondrial Damage in the Nasal Mucosa of Rats

Abstract: Exposure to PM2.5 (particulate matter ≤2.5 μm) increases the risk of nasal lesions, but the underlying mechanisms, especially the mechanisms leading to mitochondrial damage, are still unclear. Thus, we investigated the in vivo effects of PM2.5 exposure on the inflammatory response, oxidative stress, the enzyme activities of Na+K+-ATPase and Ca2+-ATPase, and the morphology and function of mitochondria in the nasal mucosa of rats. Exposure to PM2.5 occurred through inhalation of a PM2.5 solution aerosol. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 21 publications
9
68
0
3
Order By: Relevance
“…Excessive ROS exert toxic effects on cellular components via oxidative stress, inflicting direct damage to cell molecules, such as DNA, lipids and proteins, thereby affecting structure and function (Rahal et al, ). Several experimental studies have reported increased ROS production in the respiratory system in response to PM2.5 exposure both in vitro (Deng et al, ; Hong et al, ) and in vivo (Guo, Hong, et al, ). Oxidative damage was also observed in people who have been exposed to PM2.5, as reflected by the formation of 8‐hydroxy‐2′‐deoxyguanosine in urine samples (Wei et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive ROS exert toxic effects on cellular components via oxidative stress, inflicting direct damage to cell molecules, such as DNA, lipids and proteins, thereby affecting structure and function (Rahal et al, ). Several experimental studies have reported increased ROS production in the respiratory system in response to PM2.5 exposure both in vitro (Deng et al, ; Hong et al, ) and in vivo (Guo, Hong, et al, ). Oxidative damage was also observed in people who have been exposed to PM2.5, as reflected by the formation of 8‐hydroxy‐2′‐deoxyguanosine in urine samples (Wei et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…PM2.5 was collected from the ceiling (at a height of approximately 20 m) of a five‐story building located at the campus of Fudan University (31.3°N, 121.5°E), Shanghai, China. The study began in November 2014 and ended in April 2015, as described in previous studies (Guo, Dong, et al, ; Guo, Hong, et al, ; Hong et al, ). This site has a mix of industrial, construction, traffic and residential pollutants, and could thereby be considered as a representative sample of the megacity of Shanghai.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in expression patterns of proteins that regulate fusion and fission were observed in rat nasal mucosal tissues after in vivo inhalation of particulate matter (PM 2.5 ) isolated from ambient air samples from Shanghai, China (Guo et al 2017). Mnf1 and Opa1 mRNA and protein expression were increased at low and medium doses of PM 2.5 (200 and 1000 μg/m 3 ), potentially compensating for damage or in response to increased energy demands, but decreased at a high dose PM 2.5 (3000 μg/m 3 ).…”
Section: Mitochondrial Fusion and Fission As Stress Responsesmentioning
confidence: 99%
“…As we all know, mitochondria, as the unique double‐membrane subcellular organelles, provide body energy and participate in metabolic and genetic functions. Mitochondrial damage will induce the cell death even organ injury . However, to the best of our knowledge, the information about mitochondrial damage induced by ZEA via ROS has not been reviewed.…”
Section: Introductionmentioning
confidence: 99%